The Relationship Between Impostor Syndrome and Career Anxiety in Yogyakarta Students - Siti Layda Fadilah Tambak; Zahro Varisna Rohmadani (Publikasi Indonesia, 2024)
Anxiety is something that is susceptible to everyone, including someone who has just entered the work environment to continue their career. Impostor syndrome is someone who feels incapable if not for other people, meaning that he does not believe in himself and does not understand his own abilities. This study aims to determine whether there is a relationship between impostor syndrome and career anxiety in Yogyakarta students. The method in this study uses two Likert scales, namely: the CIPS (Clance Impostor Phenomenon Scale) scale and the Career Anxiety Scale (CAS). The subjects of this study were Yogyakarta students aged 20-24 years, the sample used a purposive sampling technique totaling 115 respondents. Based on the results of the study conducted using the Pearson product moment correlation technique, it showed a significance figure of p = 0.000 (p <0.05), this indicates a significant relationship between the impostor syndrome variable and career anxiety in students in Yogyakarta.